Influence of mobile phase composition on the analytical sensitivity of LC-ESI-MS/MS for the concurrent analysis of bisphenols, parabens, chlorophenols, benzophenones, and alkylphenols - Lee, Kang Mi; Moon, Han Sang; Lee, Hyeon-Jeong; Kang, Minsik; Jeong Tae Young; Son, Junghyun; Min, Hophil; Cha, Sangwon; Oh, Han Bin; Oh, Won Keun; Lee, Jaeick (Academic Press, 2023)
Phenols are significant environmental endocrine disruptors that can have adverse health effects on exposed individuals. Correlating phenol exposure to potential health implications requires the development of a comprehensive and sensitive analytical method capable of analyzing multiple phenols in a single sample prep-aration and analytical run. Currently, no such method is available for multiple classes of phenols due to elec-trospray ionization (ESI) limitations in concurrent ionization and lack of sensitivity to certain phenols, particularly alkylphenols. In this study, we investigated the influence of mobile phase compositions in ESI on concurrent ionization and analytical sensitivity of liquid chromatography-electrospray ionization-tandem mass spectrometry (LC-ESI-MS/MS) during the analysis of multiple classes of phenols, and we propose a compre-hensive and sensitive analytical method for various classes of phenols (i.e., bisphenols, parabens, benzophe-nones, chlorophenols, and alkylphenols). The proposed method was affected by 0.5 mM ammonium fluoride under methanol conditions. It enabled the concurrent ionization of all the phenols and significantly improved the analytical sensitivity for bisphenols and alkylphenols, which typically have poor ionization efficiency. This method, combined with a "dilute and shoot" approach, allowed us to simultaneously quantify 38 phenols with good chromatographic behavior and sensitivity. Furthermore, the method was successfully applied to the analysis of 61 urine samples collected from aquatic (swimming) and land (indoor volleyball and outdoor foot-ball) athletes.